PENGARUH TEKNIK JARIMATIKA TERHADAP KEMAMPUAN BERHITUNG PERKALIAN 2-9 KELAS II SDN SUKODONO 2 - Toyibah, Nisrotut; Zumrotun, Erna (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2023)
The purpose of this research is to assess students' ability to calculate multiplication 2-9 before and after applying the Jarimatika technique and to find out whether the Jarimatika technique has a significant effect on the ability to calculate Multiplication 2-9 for class II SDN Sukodono 2. The research method used is quantitative experimental design. pre-experimental one group pretest-posttest research. The population of this research was all class II students at SDN Sukodono 2 as well as a research sample of 14 students. The data collection technique for this research uses tests with instrument validation techniques using reliability and validity tests. The analysis technique for this research uses normality, homogeneity tests (as a prerequisite test for analysis) and hypotheses (Paired Sample T-Test) with the help of SPSS statistics 26. The research results obtained are based on Paired Sample T-Test analysis with a sig value. (2-tailed) of 0.000 and a significance level of 0.05, meaning 0.000 0.05, therefore Ho is rejected and Ha is accepted, this shows that the Jarimatika technique has a significant influence on the ability of class II students in calculating multiplication 2-9 , where the results of the Posttest scores after being treated with the Jarimatika technique obtained a higher score compared to the results of the Pretest scores before being given the treatment. Thus, it can be concluded that the use of the Jarimatika technique has a significant effect on students' ability to calculate multiplication 2-9 in class II at SDN Sukodono 2.